2000
DOI: 10.1002/cbm.339
|View full text |Cite
|
Sign up to set email alerts
|

Drug misuse and acquisitive crime among clients recruited to the National Treatment Outcome Research Study (NTORS)

Abstract: Background Criminal activity among drug-misusing populations can result in con-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 26 publications
(19 reference statements)
4
51
0
Order By: Relevance
“…The increased government spend on drug treatment in recent years and the widespread introduction of pro-active referral schemes, in particular the Drug Interventions Programme, has introduced greater heterogeneity amongst drug services' clients than that present a decade ago. This group of drug services' clients may present particular challenges to treatment services, by virtue of the seriousness of their drug problems (Stewart et al, 2000). Therefore, it is important that the evidence base is updated, in particular to establish more detail about the impact of treatment, for whom treatment works best and in what context.…”
Section: Contextmentioning
confidence: 99%
“…The increased government spend on drug treatment in recent years and the widespread introduction of pro-active referral schemes, in particular the Drug Interventions Programme, has introduced greater heterogeneity amongst drug services' clients than that present a decade ago. This group of drug services' clients may present particular challenges to treatment services, by virtue of the seriousness of their drug problems (Stewart et al, 2000). Therefore, it is important that the evidence base is updated, in particular to establish more detail about the impact of treatment, for whom treatment works best and in what context.…”
Section: Contextmentioning
confidence: 99%
“…Another study showed that after release from prison, the risk of reoffending is particularly high among those dependent on psychoactive substances [22]. This is because while some part of criminal behavior is likely to occur in order to finance drug use, substance use is also clearly associated with violent crime [6,2].…”
Section: Discussionmentioning
confidence: 99%
“…While some criminal behavior is likely to occur in order to finance drug use, the pharmacological effects of alcohol and drug use are also clearly associated with violent crimes [6,2].…”
Section: Introductionmentioning
confidence: 99%
“…Whether the expansion of these 'funnels' into treatment has introduced greater heterogeneity in the clients of drug services and whether treatment works for those referred from the CJS remain crucial questions. CJS-referred clients may present particular challenges to treatment services by virtue of the seriousness of their drug problems [13,14] and in terms of adherence to treatment protocols, co-operation with agency staff, continuing use of drugs, continuing offending behaviour and rates of relapse, which may adversely affect treatment outcomes in this group [15].…”
Section: Introductionmentioning
confidence: 99%